Des droits à reconnaître: les lesbiennes face à la discrimination - Bonneau, Micheline; Demczuk, Irène (Collection Les Entêtées, 1998)
Regroupant recherches et analyses, témoignages et récits personnels, ce livre rend compte de la discrimination vécue par les lesbiennes. Malgré que le Québec ait adopté une Charte des droits de la personne qui interdit toute discrimination basée sur l'orientation sexuelle, il faut reconnaître que l'adoption de ce principe d'équité n'a pas fait disparaître toute trace d'hétérosexisme dans la société. Les lesbiennes ne bénéficient pas encore d'une égalité juridique formelle, encore moins réelle.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; lesbophobie; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; shm4000; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

La conquête d'un espace public : les bars fréquentés par les lesbiennes - Chamberland, Line (Sortir de l'ombre : histoires des communautés lesbienne et gaie de Montréal, 1998)
Histoire bien documentée et inédite des communautés homosexuelles de Montréal. Longtemps victimes de brimades et de préjugés, les gais et lesbiennes sont finalement "sorti.e.s de l'ombre" et ont gagné de belles victoires durant les dernières décennies.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; his4860; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; lesbiennes; montréal; premier cycle; québec; rapports sociaux de sexe; régions géographiques; sexualité; systèmes d'oppressions; thématiques; violences

Sortir de l'ombre : histoires des communautés lesbienne et gaie de Montréal - Demczuk, Irène; Remiggi, Frank William (Des hommes et des femmes en changement, 1998)
Histoire bien documentée et inédite des communautés homosexuelles de Montréal. Longtemps victimes de brimades et de préjugés, les gais et lesbiennes sont finalement "sorti.e.s de l'ombre" et ont gagné de belles victoires durant les dernières décennies.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques; violences

Lessons from the intersexed - Kessler, Suzanne J. (Rutgers University Press, 1998)
From the moment intersexuality-the condition of having physical gender markers (genitals, gonads, or chromosomes) that are neither clearly female nor male-is suspected and diagnosed, social institutions are mobilized in order to maintain the two seemingly objective sexual categories. Infants' bodies are altered, and what was "ambiguous" is made "normal." Kessler's interviews with pediatric surgeons and endocrinologists reveal how the intersex condition is normalized for parents and she argues that the way in which intersexuality is managed by the medical and psychological professions displays our culture's beliefs about gender and genitals. Parents of intersexed children are rarely heard from, but in this book they provide another perspective on reasons for genital surgeries and the quality of medical and psychological management. Although physicians educate parents about how to think about their children's condition, Kessler learned from parents of intersexed children that some parents are able to accept atypical genitals. Based on analysis of the medical literature and interview with adults who had received treatment as interesexed children, Kessler proposes new approaches for physicians to use in talking with parents and children. She also evaluates the appearance of a politicized vanguard, many of who are promoting an intersexual identity, who seek to alter the way physicians respond to intersexuality. Kessler explores the possibilities and implications of suspending a commitment to two "natural" genders and addresses gender destabilization issues arising from intersexuality. She thus compels readers to re-think the meaning of gender, genitals, and sexuality.
Keywords: LGBTQIA2+; approches et analyses; capacitisme; care; corps; cours; discipline; ethnographie; intersexuation; premier cycle; psychologie; santé; sciences humaines; soc2014; système de genre; systèmes d'oppressions; thématiques; violences; violences médicales